Chromatic Dimensions Earthy, Watery, Airy, and Fiery. (October 2015) - Albertazzi, Liliana; Koenderink, Jan J.; van Doorn, Andrea
In our study, for a small number of antonyms, we investigate whether they are cross-modally or ideaesthetically related to the space of colors. We analyze the affinities of seven antonyms ( cold–hot, dull–radiant, dead–vivid, soft–hard, transparent–chalky, dry–wet, and acid–treacly ) and their intermediate connotations ( cool–warm, matt–shiny, numb–lively, mellow–firm, semi-transparent–opaque, semi-dry–moist, and sour–sweet ) as a function of color. We find that some antonyms relate to chromatic dimensions, others to achromatic ones. The cold–hot antonym proves to be the most salient dimension. The dry–wet dimension coincides with the cold–hot dimension, with dry corresponding to hot and wet to cold. The acid–treacly dimension proves to be transversal to the cold–hot dimension; hence, the pairs mutually span the chromatic domain. The cold–hot and acid–treacly antonyms perhaps recall Hering's opponent color system. The dull–radiant, transparent–chalky, and dead–vivid pairs depend little upon chromaticity. Of all seven antonyms, only the soft–hard one turns out to be independent of the chromatic structure.